PENGARUH TREND FASHION, PELAYANAN, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO PAKAIAN AFFIKA COLLECTION - Eriko Juliantomi Saputra; Subandrio Subandrio (UM. Bengkulu, 2023)
This study aims to determine the effect of Fashion Trends, Service, and Prices on Purchasing Decisions at the Affika Collection Clothing Store in the D1 Ketahun Market, North Bengkulu. This research is a quantitative study with a sample of 85 respondents, by using the NonProbability Sampling technique, data collection techniques using observation and questionnaires. Data analysis techniques using the classical assumption test, multiple linear regression, coefficient of determination (R2) and hypothesis testing. The results of this study can be seen from the multiple linear regression test with SPSS 24, namely Y = 3.497 + 0.743 (X1) + 0.094 (X2) + 0.147 (X3). From the hypothesis test, it is known that Fashion Trend influences purchasing decisions at Affika Collection clothing stores in the Ketahun D1 market, with the results of the T test showing a significance value of 0.000 <0.050. Service influences purchasing decisions at the Affika Collection clothing store in the Ketahun D1 market, with the results of the T test showing a significance value of 0.028 <0.050. Prices affect purchasing decisions at the Affika Collection clothing store in the Ketahun D1 market, with the results of the T test showing a significance value of 0.001 <0.050. Testing the hypothesis T test and F test shows that service quality, taste and store atmosphere together have a positive and significant effect on repurchase intention with a significance level of 0.000 <0.050, this means that Ha is accepted. In other words, Fashion Trend, Service, and Price have a positive and significant effect both partially and simultaneously on purchasing decisions at the Affika Collection clothing store in the D1 Ketahun Benegkulu Utara market. Keywords: Fashion Trend, Service, and Price